2016
DOI: 10.1038/srep35322
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomics and Chemical-Genetics Reveal Molecular Mode of Action of Valproic acid, an Anticancer Molecule using Budding Yeast Model

Abstract: Valproic acid (VA) is a pharmacologically important histone deacetylase inhibitor that recently garnered attention as an anticancer agent. Since the molecular mechanisms behind the multiple effects of VA are unclear, this study was aimed to unravel the comprehensive cellular processes affected by VA and its molecular targets in vivo using budding yeast as a model organism. Interestingly, genome-wide transcriptome analysis of cells treated with VA showed differential regulation of 30% of the genome. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…This may demonstrate an increased need for NADPH, which is generated only during the oxidative phase. VPA increases reactive oxygen species levels and induces the oxidative stress response in yeast 51,52 . Therefore, cells may require increased NADPH, which is utilized to reduce glutathione that is essential to neutralize reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…This may demonstrate an increased need for NADPH, which is generated only during the oxidative phase. VPA increases reactive oxygen species levels and induces the oxidative stress response in yeast 51,52 . Therefore, cells may require increased NADPH, which is utilized to reduce glutathione that is essential to neutralize reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that cells lacking mitochondrial respiration generally have low viability due to hypersensitivity to various stresses such as hydrogen peroxide, ethanol, and heat [ 38 , 56 , 57 ]. Furthermore, the tolerance for intracellular ROS varies depending on the difference of genetic background among the laboratory strains [ 58 ]. Taking all of the above into consideration, it is plausible that RLS of respiratory-deficient mutants is influenced by the resistance to accumulated ROS, which is different among the laboratory strains.…”
Section: Discussionmentioning
confidence: 99%
“…The β -galactosidase assay was performed to monitor the expression levels of UPRE-lacZ reporter gene as described previously [ 125 ]. Briefly, the exponentially growing wild-type (BY4741) yeast cells (OD 600 : 0.8-1) carrying 2μ UPRE-lacZ reporter plasmid ( pPW344 ; gifted by Laran T. Jensen) [ 126 ] were treated with either DMSO (solvent control) or indicated doses of KP1019 (50, 100 μg/ml; 3h) and tunicamycin (1μg/ml; 1h) in SC (Ura dropped) media.…”
Section: Methodsmentioning
confidence: 99%